Kedudukan Notaris Sebagai Pejabat Umum Ditinjau Dari Konsep Equality Before The Law - -, Edwar; Rani, Faisal A.; Ali, Dahlan (Jurnal Hukum & Pembangunan, 2019)
Notary is a general official in accordance with Law Number 2 of 2014 concerning amendments to Law Number 30 years 2014 concerning Notary Position Article 1 number 1. And for that when the notary carries out his duties as the maker of the notary deed is involved the existence of unlawful acts accordingly with Article 66 paragraph (1) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public that for the benefit of the judicial process, investigators, public prosecutors, or judges with the approval of the notary public. with the issuance of Law Number 2 of 2014 concerning Notary Position Article 66 paragraph (1) MPD is replaced with MKN meaning that the legal apparatus must be permitted by the MKN to give legal discrimination or lack of equality in the eyes of the law. in accordance with the 1945 Constitution.